1992
DOI: 10.1007/bf00571474
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of osteoarthritis of the hip due to subluxation or acetabular dysplasia

Abstract: In 59 patients, 86 hips with subluxation or hip dysplasia were examined to determine the natural course of the condition and select suitable treatment. Thirty-three percent of the joints (13/39 hips) developed early osteoarthritis from pre-osteoarthritis within an average term of 9.2 years, while the remaining, sixty-six percent (31/47 hips) developed advanced-stage osteoarthritis from early osteoarthritis within an average term of 7.8 years. Patients were classified into advanced and non-advanced groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 8 publications
0
43
0
4
Order By: Relevance
“…AHI quantifies relative acetabular support, and ARO and Sharp angles express acetabular inclination. These radiographic indices are not independent, but supplement DDH grading (Hasegawa et al, 1992;Ito et al, 2004;Nicholls et al, 2011). Nakamura et al correlated these radiographic indicators and primary OA and found the CE angle and ARO were strongly correlated to primary OA with superolateral migration (Nakamura et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AHI quantifies relative acetabular support, and ARO and Sharp angles express acetabular inclination. These radiographic indices are not independent, but supplement DDH grading (Hasegawa et al, 1992;Ito et al, 2004;Nicholls et al, 2011). Nakamura et al correlated these radiographic indicators and primary OA and found the CE angle and ARO were strongly correlated to primary OA with superolateral migration (Nakamura et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) is an important disease leading to osteoarthritis (OA) (Hasegawa et al, 1992;Jacobsen and Sonne-Holm, 2005;Lane et al, 2000), and it is well established that high stress concentrations during weight-bearing ambulation cause OA (Mavcic et al, 2008;Pompe et al, 2007). Historically, static geometric factors on radiography, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient acetabular coverage of the femoral head in developmental dysplasia of the hip (DDH) is a major cause of hip pain, dysfunction, and secondary osteoarthritis [4,7,9,10,12,21]. The Bernese periacetabular osteotomy (PAO) is commonly used for treating patients with symptomatic dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…De prognose hiervan is veelal ongunstig. Bij een dysplasie 76 JGZ-richtlijn Heupdysplasie [2] van de heup zonder (sub)luxatie ontwikkelt ongeveer 70 % op volwassen leeftijd vroegtijdige slijtage, ofwel coxartrose [13][14][15]. Bij een ge(sub)luxeerde heup treden op de leeftijd van 2 à 3 maanden vaak al veranderingen ten gevolge van de (sub)luxatie op, zoals een verkorting van de heupadductoren.…”
Section: Natuurlijk Beloopunclassified
“…Bij een dubbelzijdige luxatie ontwikkelt het kind een holle rug en kan het gaan lopen met een eendengang of waggelgang. Op (jong)volwassen leeftijd zullen meestal pijn en invalidering optreden door coxartrose [4,13,14]. De kans op coxartrose is lager wanneer kinderen vroeg worden behandeld voor DDH.…”
Section: Gevolgen Voor Het Dagelijks Levenunclassified